Five new species of the sisorid catfish genus Glyptothorax from Iran (Teleostei: Sisoridae) - Mousavi-Sabet, Hamed; Eagderi, Soheil; Vatandoust, Saber; Freyhof, Jörg (Zootaxa, 2021)
Five new species of Glyptothorax are described from Iran. Glyptothorax alidaeii, new species, from the Seimare in the Karkheh drainage, G. galaxias, new species, from the upper Karun drainage, G. hosseinpanahii, new species, from the Zohreh drainage, G. pallens, new species, from the Sirvan drainage, and G. shapuri, new species, from Shapur in the Helleh drainage. Glyptothorax silviae from the Jarrahi drainage is re-diagnosed. All six species are morphologically distinguishable by the structure of the thoracic adhesive apparatus, as well as morphometric characters and details in the colour pattern. They form distinct mitochondrial clades between 1.2% and 4.1% minimum K2P distance based on the mitochondrial DNA barcode region.